2017
DOI: 10.1002/ijc.30931
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations for disentangling a risk factor's influence on disease incidence versus postdiagnosis survival: The example of obesity and breast and colorectal cancer mortality in the Women's Health Initiative

Abstract: Often, studies modeling an exposure’s influence on time to disease-specific death from study enrollment are incorrectly interpreted as if based on time to death from disease diagnosis. We studied 151,996 post-menopausal women without breast or colorectal cancer in the Women’s Health Initiative with weight and height measured at enrollment (1993–1998). Using Cox regression models, we contrast hazard ratios (HR) from two time-scales and corresponding study subpopulations: time to cancer death after enrollment am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…This is further supported by a study on the relation between BMI and PCa progression in patients with low‐risk PCa on active surveillance 31 . However, it is possible that the net negative association between BMI and the risk of low‐risk PCa, through collider stratification bias (selection bias due to the analysis of cases only), causes spurious positive associations with BMI in prognostic analyses of this tumour group 32,33 . However, the adjustments for many important confounders would reduce the risk of collider bias influencing our results, although uncontrolled factors, such as genetics, could still be involved.…”
Section: Discussionsupporting
confidence: 63%
“…This is further supported by a study on the relation between BMI and PCa progression in patients with low‐risk PCa on active surveillance 31 . However, it is possible that the net negative association between BMI and the risk of low‐risk PCa, through collider stratification bias (selection bias due to the analysis of cases only), causes spurious positive associations with BMI in prognostic analyses of this tumour group 32,33 . However, the adjustments for many important confounders would reduce the risk of collider bias influencing our results, although uncontrolled factors, such as genetics, could still be involved.…”
Section: Discussionsupporting
confidence: 63%
“…Most research studies that have assessed BMI more than about 5 years before diagnosis has reported a positive association with all‐cause mortality and endometrial‐cancer specific mortality 28–30,35,74 . However, these associations between pre‐diagnosis BMI and cancer mortality are often limited by the fact that they cannot differentiate the extent to which the association is driven by the relationship between BMI and cancer incidence versus survival 75 . Few studies have assessed the relationship between obesity and mortality after endometrial cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the first approach we used the full‐cohort and follow‐up was from the date of baseline examination. Results from this analysis reflect the influence of the metabolic factors on both the incidence and survival of BC, however, they are unlikely to suffer from selection bias 23,24 . In the second approach, we analyzed the survival of BC cases, which allowed us to adjust for tumor characteristics, co‐morbidities and types of BC‐related treatment; factors that have a large bearing on BC‐specific survival.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigated associations either from the time of study enrollment (in the full population), or from the time of diagnosis (among cases only), but not both. Investigating either time‐line has advantages, but may also introduce certain biases that could be mitigated by investigating both time‐lines 21‐24 …”
Section: Introductionmentioning
confidence: 99%